Profiling carotenoid and phenolic compounds in fresh and canned fruit of peach cultivars: Impact of genotype and canning on their concentration - Christofi, Marina; Pavlou, Andrea; Lantzouraki, Dimitra Z.; Tsiaka, Thalia; Myrtsi, Eleni D.; Zoumpoulakis, Panagiotis; Haroutounian, Serkos; Mauromoustakos, Andy; Biliaderis, Costas G.; Manganaris, George A. (My University, 2022)
Peach (Prunus persica (L.) Batsch) is widely consumed both fresh and processed. Scarce information exists regarding the fate of phytochemicals after the peach canning process. The aim of the current study was to evaluate the compositional variability and impact of processing on the bioactive compounds profile of eight non-melting peach cultivars, both in fresh and canned forms, thermally processed with either light syrup (LS) or grape juice (GJ) as the packing medium. LC–MS analysis demonstrated that the phytochemical profile is primarily genotype dependent. Prediction profile statistics revealed that cv. ‘Andross’, a predominant clingstone peach cultivar, possessed the highest desirability score among all the examined cultivars. Free zeaxanthin and lutein remained relatively unaffected by the canning process compared to free β-carotene, whereas soluble phenolic compounds, such as neochlorogenic acid, chlorogenic acid, procyanidin B1 and catechin, showed a large decrease following canning. Using GJ, an additional source of polyphenols, as packing medium led to a reduction of losses for the bioactive compounds. Overall, the experimental findings demonstrated that, besides the thermal degradation of some sensitive to heating compounds, there is a bidirectional flow of the bioactive compounds between the fruit tissue and the liquid matrix, as balanced out by diffusion processes.
Keywords: Phenolics; Carotenoids; Nutrition; β-carotene; Prunus persica; Processing; Clingstone; Non-melting peaches; Prediction profile statistics